2021
DOI: 10.21037/apm-20-1384
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into molecular mechanisms and high-frequency core TCM for pulmonary fibrosis secondary to COVID-19 based on network pharmacology and data mining

Abstract: Background: The complication, pulmonary fibrosis (PF) secondary to COVID-19, may have a second wave of late mortality, given the huge number of individuals infected by COVID-19. However, the molecular mechanisms of PF secondary to COVID-19 haven't been fully elucidated, making the identification of novel strategies for targeted therapy challenging. This study aimed to systematically identify the molecular mechanisms and high-frequency core traditional Chinese medicine (TCM) targeting PF secondary to COVID-19 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…These cytokines, including TNF-α, can facilitate the formation of fibroblasts which in turn can lead to collagen deposition. A study on COVID-19 differentially expressed gene known to be associated with pulmonary fibrosis has identified that the TNF signaling pathway is one of the molecular pathways of pulmonary fibrosis secondary to COVID-19 [13] .Cheng et al reported an up-regulated TNF- α gene in cells infected with SARS-CoV2 [14] . Serum values of TNF- α and sTNFR1 increased in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines, including TNF-α, can facilitate the formation of fibroblasts which in turn can lead to collagen deposition. A study on COVID-19 differentially expressed gene known to be associated with pulmonary fibrosis has identified that the TNF signaling pathway is one of the molecular pathways of pulmonary fibrosis secondary to COVID-19 [13] .Cheng et al reported an up-regulated TNF- α gene in cells infected with SARS-CoV2 [14] . Serum values of TNF- α and sTNFR1 increased in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…We predicted that 149 components had therapeutic effects on COVID-19 by molecular docking, of which 20 components had good docking scores not only with antiviral targets but also with anti-inflammatory or immune-regulating targets. The 20 components were formononetin, naringenin, bicuculline, luteolin, quercetin, astragaloside IV, kaempferol, isoquercitrin, rutin, beta-carotene, salvigenin, indirubin, baicalein, calycosin, artemetin, wogonin, rosmarinic acid, apigenin, 7-methoxy-2-methyl isoflavone and emodin [ 72 94 ]. The details of components and targets were shown in Additional files 7 and 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A549 cells were added to LPS coculture to induce EMT validating the predicted outcome of network pharmacology. Evidence showed that quercetin was well validated by its docking to IL-6, TNF, and IL-1β proteins ( Yu et al, 2021 ). These findings strikingly supported the molecular docking and experimental results of our study that quercetin may exert anti-PF effects by targeted binding to TNF.…”
Section: Discussionmentioning
confidence: 99%